Household energy and recycling of nutrients and carbon to the soil in integrated crop‐livestock farming systems: a case study in Kumbursa village, Central Highlands of Ethiopia - Negash, Dugassa; Abegaz, Assefa; Smith, Jo U.; Araya, Hailu; Gelana, Bogale (Global change biology. Bioenergy, 2017)
Soil amendment with organic wastes in the Highlands of Ethiopia has been greatly reduced by widespread use of dung cakes and crop residues as fuels. This study assessed the interaction between household energy and recycling of nutrients and carbon to the soil using household survey, focus group discussions, key informant interviews, direct observations and measurements between 2014 and 2015 in Kumbursa village (Central Highlands of Ethiopia). All surveyed households were entirely dependent on biomass fuel for cooking, with production and consumption rates directly related to wealth status, which significantly varied (P < 0.001) among three farm wealth groups (poor, medium and rich). Crop residues and dung cakes accounted for 80(±3)% by energy content and 85(±4)% by dry mass weight of total biomass fuel consumption. Mean losses were 59(±2) kg ha−1 yr−1 nitrogen (109(±8) kg yr−1 per household), 13.9(±0.3) kg ha−1 yr−1 phosphorus (26(±2) kg yr−1 per household), 79(±2) kg ha−1 yr−1 potassium (150(±11) kg yr−1 per household) and 2100(±40) kg ha−1 yr−1 organic carbon (3000(±300) kg yr−1 per household). Rich farmers lost significantly more carbon and nutrients in fuel than farmers in other wealth groups. However, these losses were spread over a larger area, so losses per land area were significantly higher for medium and poor than for rich farmers. This means that the land of poorer farmers is likely to become degraded more rapidly due to fuel limitations than that of rich farmers, so increasing the poverty gap. The estimated financial loss per household due to not using dung and crop residues as organic fertilizer was 162(±8) US$ yr−1. However, this is less than their value as fuels, which was 490(±20) US$ yr−1. Therefore, farmers will only be persuaded to use these valuable assets as soil improvers if an alternative, cheaper fuel source can be found.